Schools under Mandatory Testing Can Mitigate the Spread of SARS-CoV-2 - Ingo E. Isphording; Marc Diederichs; Reyn van Ewijk; Nico Pestel (Institute of Labor Economics (IZA), 2021)
We use event-study models based on staggered summer vacations in Germany to estimate the effect of school re-openings after the summer of 2021 on the spread of SARS-CoV-2. Estimations are based on daily counts of confirmed coronavirus infections across all 401 German counties. Our results are consistent with mandatory testing contributing to containment of cases by uncovering otherwise undetected (asymptomatic) cases. Case numbers in school-aged children spike in the first week after the summer breaks but then turn not significantly different from zero. Case numbers in prime-aged age groups gradually decrease after school re-openings, arguably as a result of detected clusters through the school testing. The age group 60+ remains unaffected by the school re-openings. We conclude that the combination of mandatory testing and compulsory school attendance can provide an unbiased and near-complete surveillance of the pandemic. Thus, under certain conditions open schools can play a role in containing the spread of the virus. The trade-off between reducing contacts and losing an important monitoring device has to be taken seriously when re-considering school closures as a nonpharmaceutical intervention under the current circumstances.
Keywords: I12; I18; I28; 330; COVID-19; schooling; education; Germany